Microbiome-metabolome dysbiosis of bronchoalveolar lavage fluid of lung cancer patients - Wang, Jing; Su, Wei; Chen, Qin; Zhou, Jiemin; Wang, Xinyue; Jiang, Richeng; Li, Junling; Xing, Puyuan (Frontiers in Microbiology, 2025)
BackgroundRecent studies indicate that microorganisms significantly influence lung cancer pathogenesis. This research explores the variations in microbiota and metabolites in the lower respiratory tract between lung cancer patients and individuals with benign pulmonary lesions to identify potential diagnostic biomarkers.MethodsTwo hundred eight patients undergoing bronchoscopy at Tianjin Cancer Institute & Hospital and Tianjin Chest Hospital from October 2022 to October 2023 were screened. Ninety-five bronchoalveolar lavage fluid (BALF) was collected for metagenomic sequencing and untargeted metabolomic analysis. Comparisons of microbial diversity, taxonomic composition, and metabolite profiles were conducted between groups with lung cancer and benign lung conditions.ResultsThe cohort comprised 70 patients with lung cancer and 25 with benign lung lesions. Patients with lung cancer showed significantly reduced β-diversity (p = 0.005). Predominant microbes in lung cancer cases included Streptococcus, Haemophilus influenzae, and Veillonella parvula. A microbial-based diagnostic model differentiated lung cancer from benign lesions with an AUC of 0.931 (95%CI: 0.916–0.946). Metabolites increased in lung cancer were Citric acid, N-Acetylneuraminic acid, Oxoglutaric acid, and Neopterin, whereas L-Tryptophan, Uridine, 3-Hydroxybutyric acid decreased. The KEGG pathways suggest a significant link between microbial presence and both tumorigenesis and progression.ConclusionSpecific microbial patterns in the lower respiratory tract of lung cancer patients could assist in the auxiliary diagnosis of the disease. The notably altered microorganisms and metabolites in the BALF from lung cancer patients, as opposed to those with benign conditions, correlate with cancer initiation and advancement.